Removal of Metal Ions from Aqueous Solutions by Complexation –Ultrafiltration Hybrid Process: A Bibliographical Overview - Mimoune, Scheherazade; Belazzougui, Rafik Eddine; Benaboura, Ahmed (Journal of Membrane and Separation Technology, 2014)
Water pollution by metal ions contaminants is a worldwide alarming problem. Clean and safe water is becoming in the same time an increasing scare resource. Thus, to keep this fundamental resource available and suitable for use, water treatment methods are investigated by means of numerous research studies since the purification of water and its re-use and, in a larger scale, the environmental protection will be essential henceforth in any strategy of development. Membrane processes, in general, and ultrafiltration, in particular, develop, without stopping, since the beginning of the sixties to meet the vital need for environmental safety which justifies the policies of durable development adopted today all over the world. Thanks to its growing, ultrafiltration becomes an irreplaceable weapon in the control of pollution. It is classified as a soft and clean technology since it needs low energy consumption and ensures a notable reduction in pollution production during the treatment step. Ultrafiltration is a pressure driven membrane process with the ability to separate molecules in solution on the basis of size. A microporous ultfafiltration membrane retains species with molecular weight higher than its cut off, while small molecules as solvents and microsolutes can pass freely through it. Thus, metal ions aren’t rejected by ultrafiters. However, ultrafiltration can be used to remove metal ions from aqueous solutions by coupling the process with complexation. Indeed, the complexation of metal ions using water soluble polymers as substrates is able to expand artificially the size of the metallic species so as to make possible their rejection by the microporous ultrafilters. The complexation –ultrafiltration hybrid process was first suggested at the end of the sixties by A. S. Michaels. Since then, many studies have shown its effectiveness in the treatment of aqueous solutions containing metal ions. This paper gives an overview of academic studies that illustrate and demonstrate the efficiency and the promising of the hybrid process in the purification of water from metal ions contaminants beforehand sequestered by adequate water –soluble macromolecular substrates.